Galling by Trichilogaster sp. suppresses the growth of Acacia auriculiformis saplings - Christine H. Sanderson; Ryan Zonneveld; Matthew F. Purcell; S Raghu (Biological Control)
Pre-release efficacy assessments (PREAs) are used in weed biological control to predict the potential impact of prospective agents. These assessments enable the most damaging agents to be prioritised for host testing and release. Further, the inclusion of this information in release applications enables regulators to consider the benefits of an agent alongside any risks. We conducted a PREA to evaluate the efficacy of Trichilogaster sp., a galling wasp that is being considered for release in Florida to control invasive earleaf acacia, Acacia auriculiformis. This species is multivoltine and primarily galls vegetative buds. We performed a glasshouse trial exposing A. auriculiformis saplings to one generation of the gall wasp to determine the effect of galling on plant performance. We monitored the growth parameters and development of exposed and unexposed saplings every three weeks for twelve weeks. Above-ground and below-ground biomass were measured at the completion of the trial. One generation of galling reduced sapling height by 37.44 % (±5.57), above-ground biomass by 32.19 % (±4.00), and below-ground biomass by 38.26 % (±7.47). Galling also significantly reduced the other key growth parameters of stem weight, leaf weight, total branch length, and the number of nodes, shoot tips, and leaves. This Trichilogaster species significantly damages juvenile A. auriculiformis plants and could be an effective classical biological control agent if released in Florida, especially if it is not limited by a specialist third trophic level.